MACROECONOMIC VARIABLE AND PROPERTY STOCK MARKET VOLATILITY DURING AND AFTER PANDEMIC - Nicholas, Nicholas; Ekadjaja, Margarita (Graduate Program of Universitas Tarumanagara, 2024)
Since the pandemic, stock market activities have become increasingly popular among the public. Therefore, it is important to know what factors influence the stock price of a company so that it can be more optimal in buying and selling or investing in shares for both parties, namely investors/traders and also issuers/companies. It is important for investors to know the economic conditions around them to decide whether to buy shares as an investment or not. And for companies to make the right financial decisions in accordance with the surrounding macroeconomic conditions so that share prices can be more optimal. This research can provide insight for investors and companies so they can make wise decisions. For investors, this research is useful for assessing what stock prices should be or future stock prices by considering the surrounding economic conditions. Meanwhile, for companies, this research is useful for providing insight so they can prepare for the worst and predict share prices, then make good decisions to optimize their share prices. Therefore, this research aims to determine the factors that influence stock market prices from the external side, including interest rates, inflation, exchange rates and economic growth which are proxied by gross domestic growth in the property sector stock market listed on the IDX during and after the pandemic. Data processing uses Eviews and shows the results that the variables of interest rates, exchange rates and GDP have a negative effect on fluctuations in the stock market price index. Meanwhile, inflation has a positive effect on fluctuations in the stock market price index.